درجة تطبيق مديري المدارس الثانوية لمفهوم الأولويات التربوية في مدينة الطائف من وجهة نظر المشرفين التربويين - المطيري، فهيد بن منور; بكر، عبدالقادر بن صالح بن عبدالقادر (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2017)
هدفت الدراسة إلى التعرف على درجة تطبيق مديري المدارس الثانوية لمفهوم الأولويات التربوية في مدينة الطائف من وجهة نظر المشرفين التربويين، واتبعت الدراسة المنهج الوصفي المسحي، وتمثلت أداة الدراسة في استبانة مكونة من جزأين رئيسيين: الأول يتعلق بالمعلومات العامة, والثاني متعلق بمحاور الاستبانة, وتضمن ثماناً وخمسين فقرة موزعه على مجالين لمفهوم الأولويات التربوية وهما مجال المهام الإدارية, مجال المهام الفنية وتكونت عينة الدراسة من 176 مشرفاً تربوياً، وتم استخدام معامل الارتباط بيرسون, ومعامل كرونباخ ألفا لحساب صدق وثبات الأداة, واستخدمت النسب, والمتوسطات الحسابية, والانحراف المعياري لدرجات التطبيق, كما استخدم تحليل التباين الأحادي (ANOVA), وكذلك اختبار ت (T test) للكشف عن دلالة الفروق الإحصائية، وقد تبين من النتائج أن درجة تطبيق مديري المدارس الثانوية لمفهوم الأولويات التربوية في مجال المهام الإدارية ككل مرتفعة بينما جاءت في مجال المهام الفنية بدرجة متوسطة، وتبين من النتائج أن المهام الإدارية التي احتلت مراتب متقدمة في أولوياتها كانت في غالبها مهام ظاهرة وملموسة النتائج عند تقييم عمل المدير, بينما تأخرت المهام التي في غالبها مهام تنظيمية وتخطيطية، كما أن المهام الفنية التي احتلت مراتب متقدمة في أولوياتها كانت في غالبها مهام ظاهرة وملموسة النتائج وكذلك المهام التي تهتم بالطالب واحتياجاته, بينما تأخرت المهام التي تهتم بالمعلم وتلمّس احتياجاته، ولا توجد فروق ذات دلالة إحصائية عند مستوى الدلالة 0.05=α, بين متوسطات استجابات أفراد مجتمع الدراسة من المشرفين التربويين حول درجة تطبيق مديري المدارس الثانوية لمفهوم الأولويات التربوية ومجالاتها تعزى للمؤهل العلمي باستثناء مجال المهام الإدارية لصالح فئة الدراسات العليا, ولا توجد فروق ذات دلالة احصائية عند مستوى الدلالة 0.05=α تعزى للخبرة و الدورات ومجال الإشراف.
The study aimed at identifying the degree of application of concept of educational priorities by secondary school principals in the city of Taif from the point of view of the supervisors.The study used a descriptive survey approach.Study tool was a questionnaire composed of two main parts : The first part is related to public information, and the second part is related to the points of questionnaire, and it include and fifty - eight items distributed on two areas of the concept of educational priorities, namely the field of administrative tasks, the field of technical tasks.The study smple consisted of 176 educational supervisors. The study used the Pearson correlation coefficient, and Cronbach's alpha coefficient to calculate the reliability and validity of the tool, and used ratios, arithmetic mean, and standard deviation scores for the application, (ANOVA) as well as the T - test to detect statistical significance of differences.Results showed that the degree of application the concept of educational priorities by secondary school principals in the field of administrative tasks as a whole was high but in the field of technical tasks was moderate the administrative tasks that occupied advanced ranks in priority tasks were predominantly visible and tangible results when evaluating the work of a principle, while the tasks that are mostly regulatory and planning functions were at the end.the technical tasks that occupied advanced ranks in priority tasks were mostly in the visible and tangible results and tasks that are interested in student needs, while tasks related to the teachers were at the end.No statistically significant differences at the level of α = 0.05 between the averages of responses from members of the study population of supervisors about the degree of application of the concept of educational priorities by secondary school principals and its fields, attributed to the scientific qualification, except for the scientific field of administrative tasks in favor of Graduate studies, and there are no statistically significant differences at the level of α = 0.05 attributed to the experience and courses and field supervision
Keywords: التربية -- الأولويات التربوية -- المشرفين التربويين -- الإدارة المدرسية -- المدارس الثانوية -- مدينة الطائف